Sustainable conversion of coconut tree residues into activated carbon using steam activation - Chaiya, Chaiyan; Jansri, Ektinai (Frontiers in Engineering Innovation Research, 2026)
This study investigated the potential of five types of coconut tree residues, namely petiole base, spadix, exocarp, spathe, and rachilla, as precursors for activated carbon production through steam activation. This approach provides a sustainable pathway for valorizing agricultural residues while reducing the use of chemical activating agents in the production process. Elemental analysis revealed that the raw materials contained carbon in the range of 36.44-43.28 %, with spathe showing the highest carbon content. Proximate analysis further indicated that the raw materials were mainly composed of volatile matter, ranging from 69.41 to 72.74 %, while the fixed carbon content ranged from 15.33 to 21.34 %, reflecting the typical characteristics of lignocellulosic biomass suitable for conversion into carbon materials. After carbonization at 500 °C for 2 h, the resulting chars exhibited yields of 24.81-33.01 %, specific surface areas of 67.30-330.18 m2/g, and average pore diameters of 1.5-1.7 nm, with the exocarp-derived char showing the highest surface area at this stage. The chars were subsequently activated with steam at 500, 600, and 700 °C. The results showed that increasing the activation temperature markedly enhanced the specific surface area of the activated carbons, while the product yield decreased with increasing temperature. This trend was associated with the reaction between steam and carbon and the progressive development of porous structures. At 700 °C, the spathe-derived activated carbon exhibited the highest surface area of 778.64 m2/g, followed by rachilla, exocarp, spadix, and petiole base. In addition, increasing the activation temperature promoted pore widening, with the average pore diameter at 700 °C increasing to 1.9-2.2 nm, indicating a transition from microporous structures toward the boundary between micropores and mesopores. These findings demonstrate that spathe, rachilla, and exocarp are promising coconut tree residues for activated carbon production using steam activation and represent a sustainable route for the utilization of lignocellulosic biomass wastes.